Proper-orthogonal-decomposition study of turbulent near wake of S805 airfoil in deep stall - Wu, Yanhua (2018)
A proper-orthogonal-decomposition analysis was performed on the turbulent flow in the near-wake region of an S805 airfoil in deep stall at an angle of attack of 30 deg. The flow was measured using tomographic particle image velocimetry at a Reynolds number of 4600. Instantaneous turbulence structures, which were significant contributors to the first two proper-orthogonal-decomposition modes, were studied. These structures included the large-scale Kármán vortex and small-scale shear-layer vortices that were interacting with the Kármán vortex. An interesting correspondence was observed between the rotational vectors in proper-orthogonal-decomposition modes 4 and 5 and the locations of the leading-edge shear-layer vortices in the flowfields, which were major contributors to these two modes. Similarity was found in the autospectral functions computed from the velocity fields, which were significant contributors to the first five proper-orthogonal-decomposition modes. The wavelengths corresponding to the peak values of autospectral functions could be related to the size of the induced flows by the Kármán vortex and the streamwise spacing of the shear-layer vortices.